2019
DOI: 10.33736/jcest.1434.2019
|View full text |Cite
|
Sign up to set email alerts
|

Porosity, Permeability and Microstructure of Foamed Concrete Through Sem Images

Abstract: This paper examined the foamed concrete (FC) for permeability of total and capillary water absorption, at 28 days of air sealed curing. The microstructure of 15 selected FC specimens was investigated to determine permeability in relation to porosity and density using Scanning Electron Microscopy (SEM) images. The FC specimens of the densities (1100, 1600, and 1800) kg/m3 were made using fine sand and brick aggregates with toner and MK inclusion as additives. The microstructural investigation of the FC revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Lower water absorption in reinforced specimens indicates lower environmental harm, confirming the matrices’ lower permeability. With the addition of fibers beyond 2%, due to the uneven distribution of fibers in the concrete matrix, the volume of pores increased, consequently reducing the concrete density and providing more space in the matrix to absorb water and a higher water absorption rate [ 41 , 42 ]. The findings show that raising the fiber volume fraction changed the distribution and size of air voids in the matrices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower water absorption in reinforced specimens indicates lower environmental harm, confirming the matrices’ lower permeability. With the addition of fibers beyond 2%, due to the uneven distribution of fibers in the concrete matrix, the volume of pores increased, consequently reducing the concrete density and providing more space in the matrix to absorb water and a higher water absorption rate [ 41 , 42 ]. The findings show that raising the fiber volume fraction changed the distribution and size of air voids in the matrices.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, De Schutter et al [ 44 ] confirmed that a higher porosity volume in the concrete matrix causes increased sample degradation due to a higher water absorption rate. Shawnim et al [ 42 ] found that an uneven spreading of large holes might increase permeability, leading to greater water absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the load-carrying capacity in compression is primarily a function of the density. Besides, Shawnim & Mohammad [20] highlighted that at the higher densities, the compressive strength is not influenced by the distribution of air voids, but rather by the more uniform distribution of voids. Lim et al [21] also mentioned that the production of LFC with finer sand results in a more uniform distribution of air voids compared to coarse sand.…”
Section: Load Carrying Capacity In Compressionmentioning
confidence: 99%
“…García et al posited that the air void content in a mixture depends mainly on the percentage of the clusters of fibers in the mixture [28], while Schutter et al [29] noted that a more porous generated CCM results in increased degradation of a sample, caused by increased overall water absorption. Shawnim et al [30] pointed out that the uneven distribution of large-sized pores can lead to high permeability, resulting in increased water absorption, while Ramamurthy et al [31] observed that smaller air voids result in lower porosity and vice versa. Figure 5 confirms that increasing the fiber fraction beyond 4% resulted in altered air void distribution and sizes in the CCM.…”
Section: Compressive Strengthmentioning
confidence: 99%